Comparative evaluation of triacylglycerols, fatty acids, and volatile organic compounds as markers for authenticating sesame oil. Issue 1 (1st January 2018) - Mansur, Ahmad Rois; Jeong, Ha-Ram; Lee, Bong Han; Koo, Minseon; Seo, Dong-Ho; Hwang, Sun Hye; Park, Ji Su; Kim, Dae-Ok; Nam, Tae Gyu
ABSTRACT: Sesame oil is a high-value edible vegetable oil, and concern about its authenticity has gained much attention for commercial and consumer health reasons. The present study compares the application of triacylglycerols (TAGs), fatty acids, and volatile organic compounds (VOCs) as markers for discriminating pure sesame oils from those adulterated with corn or soybean oils. The profiles of TAGs, fatty acids, and VOCs in oil samples were established by high-performance liquid chromatography-evaporative light scattering detector, gas chromatography (GC)-flame ionization detector, and GC-time-of-flight mass spectrometer, respectively. Data from six TAGs, seven fatty acids, and six VOCs were employed separately to classify oil samples via principal component analysis (PCA). The PCA results indicate that VOCs show much greater promise than TAGs and fatty acids for detecting corn or soybean oil adulteration (approximately 5% w/w content) of sesame oils.